Diene Synthesis by the Reductive Transposition of 1,2-Allenols - Rinaolo, Vincent J.; Robinson, Emily E.; Diagne, Abdallah B.; Schaus, Scott E.; Thomson, Regan J. (Synlett, 2019)
Monoalkyl diazene species are versatile intermediates that have enabled many useful synthetic transformations in complex chemical environments. Herein we report the reductive transposition of 1,2-allenols for the direct synthesis of dienes through an alkene walk process.
Keywords: allenol; diene; reduction; transposition; diazene